Peran Musyawarah Guru Mata Pelajaran PAI dalam Meningkatkan Kompetensi Pendidik Sekolah Menengah Pertama di Kabupaten Padang Pariaman, Sumatera Barat, Indonesia - Zarmis Zarmis; Ahmad Lahmi; Aguswan Rasyid (Arfannur, 2020)
This study aims to describe and analyze the role of the Islamic Religious Education Subject Teacher Forum in improving the competence of junior high school educators in Pariaman Regency, West Sumatra. The focus of this research was placed at the Junior Secondary School Islamic Religious Education Subject Teacher Forum in Padang Pariaman Regency, West Sumatra, Indonesia. This type of research is descriptive qualitative. Meanwhile, the research data sources were the management of the MGMP PAI SMP and Islamic Religious Education teachers, the supervisor coordinator, the coordinator of Islamic Religious Education subjects and the principal. In line with that, as a data collection instrument the researcher used observation, interviews, and documentation. To ensure the validity of the data, a triangulation process was used. Then the data collected was analyzed through three levels, namely; data display, data reduction, and drawing conclusions. The results of this study found three main things, namely: first, efforts to increase pedagogic and professional competence have been carried out by MGMP PAI, but a number of planned programs have not been fully realized, because they are hindered by the distance from the far area, lack of motivation of educators to improve self quality, and besides that there are still many educators who are not technologically illiterate. Second, the challenges faced are too much teaching load, the planned MGMP PAI schedule is not fully used by educators for PAI MGMP activities, the PAI MGMP membership with the status of civil servants tends to experience a decrease in number due to entering retirement. Third, some educators are not ready to implement learning innovations. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis peran Musyawarah Guru Mata Pelajaran Pendidikan Agama Islam dalam meningkatkan kompetensi pendidik Sekolah Menengah Pertama di Kabupaten Pariaman, Sumatera Barat. Lokus penelitian ini ditempatkan di Musyawarah Guru Mata Pelajaran Pendidikan Agama Islam Sekolah Menengah Pertama di Kabupaten Padang Pariaman, Sumatera Barat, Indonesia. Jenis penelitian adalah kualitatif deskriptif. Sedangkan sumber data penelitian adalah pengurus MGMP PAI SMP dan guru Pendidikan Agama Islam, koordinator pengawas, koordinator mata pelajaran Pendidikan Agama Islam dan kepala sekolah. Sejalan dengan itu, sebagai instrumen pengumpulan data penulis menggunakan observasi, wawancara, dan dokumentasi. Untuk memastikan keabsahan data digunakan proses trianggulasi. Kemudian data yang dikumpulkan dianalisis melalui tiga level, yaitu; display data, reduksi data, dan penarikan kesimpulan. Adapun hasil penelitian ini menemukan tiga hal pokok, yaitu: pertama, upaya peningkatan kompetensi pedagogik dan profesional telah dilakukan oleh MGMP PAI, tetapi sejumlah program yang direncanakan belum terealisasi sepenuhnya, karena terhalang oleh jarak wilayah yang berjauhan, kurangnya motivasi pendidik untuk meningkatkan kualitas diri, dan selain itu pendidik masih banyak yang gagap teknologi. Kedua, tantangan yang dihadapi berupa beban mengajar yang terlalu banyak, jadwal MGMP PAI yang direncanakan tidak sepenuhnya digunakan oleh pendidik untuk kegiatan MGMP PAI an sich, keanggotaan MGMP PAI berstatus pegawai negeri sipil cenderung mengalami menurunan jumlah karena memasuki purna bakti. Ketiga, pendidik sebagian belum siap menerapkan inovasi pembelajaran.